Transfer of training determinants in Indian public organisations. (2nd August 2019) - Sahni, Jolly; Mohamed, Norshidah
The paper investigates the transfer of training determinants in selected Indian public organisations. The research uses the Kirkpatrick framework and context, input, process, and product (CIPP) model to develop and confirm a research model. Using a cross-sectional survey design, a total of 115 questionnaires were distributed to training participants. Data was analysed using structural equation modelling technique. Findings indicate that employee's overall satisfaction, training component, perceived training utility and trainer's performance relate to training effectiveness. Further, work environment and perceived transfer performance relate to transfer of training. Participant's perceived training effectiveness, motivation to transfer training and training design jointly determine the transfer of training. The research contributes to the literature through advancing the understanding of transfer of training determinants in Indian public organisations. For training professionals, the model and instrument could be used for future training evaluation. One key limitation of the research is that the findings cannot be generalised, as the sample is not random.